Betrayal of the Innocents : Desire, Power, and the Catholic Church in Spain - Mitchell, Timothy (University of Pennsylvania Press, 2017)
In recent times, priests charged with sexual abuse have captured headlines and bankrupted dioceses all over the United States. But these cases have not exacerbated class conflict, threatened the stability of the government, despoiled national folklore, obsessed several literary generations, or led to the murder of thousands of priests. Spain has seen all of this and more. Timothy Mitchell's powerful and compelling book is the first to assess the long-term consequences of clergy sexual activity in another culture. Mitchell shows how the extreme idealization of motherhood promoted by Spanish Catholicism greatly increased the frequency of exploitative events. The resulting spiritual and social conflicts affected every area of cultural life: film, literature, law, show business, child-rearing, psychiatry, and gynecology are among the many Mitchell explores. When anticlerical writers and politicians were crushed by Franco with the aid of fascist women's organizations, Spanish children were subjected to another long period of authoritarian sexuality. The battle for custody of their minds is far from over; Betrayal of the Innocents concludes with a look at current trends and salutes new generations of Spaniards recovering from a legacy of clergy abuse unlike anything in American experience.